Pengaruh Sosial Media dan Customer Relationship Marketing Terhadap Kepuasan Konsumen dan Minat Beli Ulang Pada Produk Maybelline di Kota Semarang - Daneswara Febbyana Pratama; Mahmud Mahmud (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Digital technology has made social media not only a promotional tool but also an effective interaction platform. This study examines the role of social media and strong customer relationship marketing, where the integration of interesting content and personal communication is key to increasing satisfaction and repurchase intention. Social media is a digital platform that allows users to interact, share content, and build social networks online. Customer relationship marketing focuses on building long-term relationships between business managers and customers in order to maintain business continuity. The purpose of this study is to determine how social media and Customer Relationship Marketing influence repurchase intention through consumer satisfaction of Maybelline products in Semarang City. Data were collected using a questionnaire (Google Form) with 170 respondents. This study used Smart-PLS analysis. The results of this study indicate that social media and customer relationship marketing have a positive and significant effect on customer satisfaction. Then, customer relationship marketing has a positive and significant effect on repurchase intention, but social media does not significantly affect repurchase intention.